Ethics Versus Success? The Acceptance of Unethical Leadership in the 2016 US Presidential Elections - Morais, Catarina; Abrams, Dominic; Randsley de Moura, Georgina (Frontiers in Psychology, 2020)
Before and after the 2016 US Presidential Election, this research examined Trump and Clinton supporters’ attributions about behavior of each leader, both of whose ethicality had been publicly questioned. American voters (N = 268) attributed significantly more dispositional factors to the outgroup leader than to the ingroup leader. Moreover, when the ingroup candidate won the election (i.e., among Trump supporters), unethical leadership subsequently became more acceptable and there was less desire to tighten the election process when dealing with unethical candidates. The opposite pattern was found among voters whose ingroup candidate lost the election (Clinton supporters). The results and implications are discussed more acceptable and there was less desire to tighten the election process when dealing with unethical candidates. The opposite pattern was found among voters whose ingroup candidate lost the election (Clinton supporters). The results and implications are discussed.